Education, Rationality and Emotion in Tessitura of Socio-Technical Networks (Revista Brasileira Multidisciplinar, 2010)
This work aims to reflect on the concepts of Humberto Maturana, a Chilean biologist, who rescues the crossover tension between emotion and rationality, based on the proposals of two doctoral studies in an environmental multidisciplinary program, at UERJ (PPGMA). The issue of Eco-subjectivities and Distance Education will be analyzed in the light of the ideas of anthropology of science and of techniques as a contribution to the restoration of the sociotechnical network of emotion in educational processes.
Keywords: Emotion; Eco-subjectivities; Distance Education; Sociotechnical networks; Biology of Knowledge.